2019
DOI: 10.1186/s12967-019-1813-7
|View full text |Cite
|
Sign up to set email alerts
|

AntAngioCOOL: computational detection of anti-angiogenic peptides

Abstract: Background Angiogenesis inhibition research is a cutting edge area in angiogenesis-dependent disease therapy, especially in cancer therapy. Recently, studies on anti-angiogenic peptides have provided promising results in the field of cancer treatment. Methods A non-redundant dataset of 135 anti-angiogenic peptides (positive instances) and 135 non anti-angiogenic peptides (negative instances) was used in this study. Also, 20% of each class were selected to construct an i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…The first and most important consideration for developing a promising computational model is to construct a reliable benchmark dataset. In this study, the benchmark dataset was obtained from the work of Ramaprasad et al [27], which has been used for developing recent prediction models of anti-angiogenic peptides [28,29]. Initially, the benchmark dataset had 257 peptide sequences in the anti-angiogenic class as derived from various articles and patents.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The first and most important consideration for developing a promising computational model is to construct a reliable benchmark dataset. In this study, the benchmark dataset was obtained from the work of Ramaprasad et al [27], which has been used for developing recent prediction models of anti-angiogenic peptides [28,29]. Initially, the benchmark dataset had 257 peptide sequences in the anti-angiogenic class as derived from various articles and patents.…”
Section: Methodsmentioning
confidence: 99%
“…Their comparison results indicated that the best model based on generalized linear model yielded 86% accuracy in which such model utilized the top 200 informative features for model building. Recently, Zahiri et al [29] developed the AntAngioCOOL R package and executed performance comparisons amongst various machine learning techniques and types of peptide features. Based on their results on performance comparisons, regression, and survival trees model employing descriptors consisting of pseudo amino acid composition, k -mer composition, k -mer composition (reduced alphabet), physico-chemical profile, and atomic profile yielded the highest accuracy of 77% over an independent validation test from 1 round of random split.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Random forest was the approach followed by both Yang [ 25 ] and Barman [ 26 ]. The approach followed by Leite [ 27 ], Zahiri [ 28 ], and Mei [ 29 ], were k-nearest neighbors, multilayer perceptron, and AdaBoost, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, researchers work on different viruses to predict their PPI networks. Zhao predicted HIV1-human PPI network [ 28 ], Khorsand uncovered Alphainfluenzavirus-human PPI network [ 29 ], Ray predicted HCV-human PPI network [ 30 ], Chan revealed west nile virus-human PPI network [ 31 ], and Duran worked on herpesvirus-human PPI network [ 32 ].…”
Section: Introductionmentioning
confidence: 99%